Исследование эффективности применения теплонасосных установок для нужд теплоснабжения в условиях Украины - Бикмаев, С. Р.; Губчинский, М. В.; Усенко, А. Ю.; Федоров, С. С.; Форись, С. Н.; Шишко, Ю. В. (НТУ "ХПИ", 2010)
The article presents the results of theoretical researches of heat pumps efficiency. Were identified economic and environmental potential of these equipment. The influence of temperature heat source and cool heattransfer agent on transformation coefficient concerning Ukrainian consumers was established. It is shown the use of heat pumps can significantly reduce emissions of the greenhouse gases in the atmosphere
Keywords: источники теплоты; нетрадиционные источники энергии; хладагент; коэффициент преобразования теплоты